ENVIRONMENTAL SAFETY ENSURING OF GAZPROM TRANSGAZ KRASNODAR COMPRESSOR STATION SHAKHTINSKAYA - Ageeva, N. V.; Dymnikova, O. V. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2018)
The article considers the impact of the production activities of a specific power engineering facility Gazprom Transgaz Krasnodar Compressor Station Shakhtinskaya on the environment. It offersmeasures for more efficient organization of ecologically safe operation of the station. The recommended system will not only reduce the amount of waste, but also allow heat recovery andsignificantly energy saving, including the production of hot water.